1992
DOI: 10.1063/1.107586
|View full text |Cite
|
Sign up to set email alerts
|

Dishing effects in a chemical mechanical polishing planarization process for advanced trench isolation

Abstract: We report the first detailed study of dishing effects in chemical mechanical polishing (CMP) of oxide films, observed during the development of an advanced CMP-only trench isolation process. The degree of dishing has been determined for field widths ranging from 0.3 μm to 4 mm and was found to be highly pattern geometry (field width) sensitive, increasing from ∼0 nm at a field width of 5 μm and below to 200 nm at 4 mm. Although this dishing effect makes complete planarization in a large field oxide region (on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 2 publications
1
10
0
Order By: Relevance
“…The oxide dishing is clearly very sensitive to oxide trench width and increases as the trench width increases. This predicted trend is consistent with the experimental observations [5,6]. Furthermore, the trench width has a stronger influence on field oxide dishing than the pattern density.…”
Section: Effect Of Pattern Geometrysupporting
confidence: 90%
See 1 more Smart Citation
“…The oxide dishing is clearly very sensitive to oxide trench width and increases as the trench width increases. This predicted trend is consistent with the experimental observations [5,6]. Furthermore, the trench width has a stronger influence on field oxide dishing than the pattern density.…”
Section: Effect Of Pattern Geometrysupporting
confidence: 90%
“…Significant research efforts have been made to investigate the effects of process parameters and pattern geometry on oxide dishing for STI CMP [5][6][7][8][9]. In these studies, it was found that the amount of oxide dishing is sensitive to pattern density, trench width and overpolishing time.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the endpoint of the process is difficult to determine and the dishing phenomenon is often observed. [5][6][7] Furthermore, the CMP method is not applicable to the fabrication of large-area TFT arrays because the glass surface is not as flat as the wafer surface is.…”
mentioning
confidence: 99%
“…[1][2][3] The applications of CMP are shallow trench isolation (STI), planarization of inter-layer dielectric (ILD), the formation of contacts and interconnects, and so on. [4][5][6][7][8][9][10][11][12][13] CMP is a hybrid material removal process where chemical reaction with slurry chemicals and mechanical abrasion with abrasives complement each other. [14][15][16][17] With the advent of sub-20 nm device era, CMP faces many challenges such as provisions of nanometer level planarity and sub-nanometer level roughness to wafer surfaces without any surface damage, acquisition of versatile selectivity of removal rate (RR) and so on.…”
Section: Introductionmentioning
confidence: 99%